Implementasi Kebijakan Peraturan Daerah Nomor 10 Tahun 2013 Tentang Pengelolaan Limbah Berbahaya dan Beracun (B3) Di Kabupaten Karawang - Selly Anggraini; Rachmat Ramdani; Mochamad Faizal Rizki (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to study and know about the Implementation of Regional Regulation Policy Number 10 of 2013 concerning Hazardous and Toxic Waste Management (B3) in Karawang Regency. The theory used is George III's Policy Implementation theory theory in Wiwi Syahriawiti (2020) with four indicators, namely (1) communication; (2) resources; (3) disposittions; and (4) bureaucratic structure. This research uses qualitative descriptive method with data collection techniques carried out through interviews, observations and documentation Study. The results of the discussion of this study show that DLHK has carried out its duties quite optimally, but there is still a need for some improvements that will maximize the performance of DLHK.